2011
DOI: 10.1590/s0103-90162011000100010
|View full text |Cite
|
Sign up to set email alerts
|

Salt stress induced damages on the photosynthesis of physic nut young plants

Abstract: Salinity is a major limiting factor to crop productivity in the world especially in semiarid regions. The aim of this study was to evaluate the photosynthetic resistance of Jatropha curcas (L.) young plants subjected to salt stress. The experiment was carried out in a completely randomized design with treatments in a 2 × 3 factorial: two NaCl levels (0 and 100 mmol L -1 ) and three harvest times: 7 and 14 days of salt exposure and three days of recovery. Leaf Na + and Cl -concentrations and the K + /Na + ratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
79
1
15

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(107 citation statements)
references
References 17 publications
12
79
1
15
Order By: Relevance
“…Notwithstanding, g s significantly lowered under mild salt stress in all the plant combinations and for the time exposures, which corroborates a previous finding that g s are very sensitive to salt [49,61]. In addition, the Rubisco carboxylase activity [62]. In contrast, stomatal limitations to photosynthesis should occur in A/12 at T1 and T2 since no changes in A N /Ci were observed under salinity [63].…”
Section: Discussionsupporting
confidence: 89%
“…Notwithstanding, g s significantly lowered under mild salt stress in all the plant combinations and for the time exposures, which corroborates a previous finding that g s are very sensitive to salt [49,61]. In addition, the Rubisco carboxylase activity [62]. In contrast, stomatal limitations to photosynthesis should occur in A/12 at T1 and T2 since no changes in A N /Ci were observed under salinity [63].…”
Section: Discussionsupporting
confidence: 89%
“…1). Although limited space for root development might have contributed to this result, other authors have reported that root systems are less affected by salinity than are shoots, despite the fact that the roots receive greater exposure to the saline environment (Cavalcanti et al 2005;Silva et al 2011).…”
Section: Resultsmentioning
confidence: 97%
“…Flexas et al (2008), Silveira et al (2010) e Kusvuran (2012) afirmam que a salinidade elevada da água de irrigação exerce efeito prejudicial no processo de abertura estomática das plantas, por aumentar a resistência à difusão de CO 2 , o que foi observado nas plantas irrigadas com a água de 4,5 dS m -1 , principalmente nas plantas com biofertilizante e cobertura morta, em que a g s foi reduzida de 0,08, nas plantas irrigadas com água de baixa salinidade, para 0,04 mol m -2 s -1 , nas irrigadas com água de alta salinidade. Silva et al (2011) reportam que ocorre a diminuição da fotossíntese, associada a baixa condutância estomática foliar, em plantas submetidas a condições de salinidade hídrica.…”
Section: Resultsunclassified
“…Submetidas a estresses abióticos ou ambientais, as plantas apresentam sintomas de alterações no estado funcional das membranas dos tilacóides dos cloroplastos, que provocam mudanças nas características dos sinais de fluorescência, quantificados nas folhas pela fluorescência inicial (F 0 ), máxima (F m ) e variável (F v ) da clorofila a, além do rendimento quântico potencial (F v /F m ) (CHA-UM; KIRMANEE, 2011;SILVA et al, 2011).…”
Section: Introductionunclassified